SUCCESSFUL PROFESSIONAL PHOTOGRAPHER - VALENZUELA, ROBERTO (ROCKY NOOK, 2020)
Learn how to confidently build a thriving and profitable career as a professional wedding or portrait photographer! For nearly a decade, renowned wedding and portrait photographer Roberto Valenzuela has been sharing his vast knowledge and unique, systematic approach to making photographs as he has taught workshops around the world and written five critically acclaimed and bestselling books that cover composition, posing, lighting, and wedding photography (his Picture Perfect and Wedding Storyteller series of books). He has helped countless photographers improve their craft. But the truth is that you can create the most amazing photos...yet still have a failing business. And what's the point of being a great photographer if you can't build a career, pay your bills, and feed your family? In order to create a thriving business, you need a different kind of knowledge and a new set of tools to succeed. In The Successful Professional Photographer , for the first time Roberto turns his focus on the business and marketing of your photography so that you can build and sustain a highly profitable business as a wedding and portrait photographer. Roberto shares all his hard-earned knowledge regarding finding clients, marketing and presenting your work, and getting paid what you deserve. Topics include: • Best practices and strategies for Instagram, YouTube, and Facebook • Being found through SEO • Promoting yourself and your work • The role that testimonials and reviews play in your success • Creating long-term client relationships • Forming personal connections with clients with promo videos • Why you should feature your work in publications • Pricing your work and the gentle art of the up-sell • Understanding and conveying the crucial importance of selling prints While the photographs you create are the core of your work as a photographer--being exceptional at your craft is a must--that's only half of the formula you need for building and sustaining success. The other half of the formula is here, in The Successful Professional Photographer . Implement the strategies and techniques outlined here, and you'll have everything you need to succeed and build a long, prosperous, fulfilling career as a wedding or portrait photographer. Foreword by Luke Edmonson TABLE OF CONTENTS Part I: How to Stand Out Chapter 1: Unleashing Instagram's Business Potential Chapter 2: SEO for Portrait and Wedding Photographers Chapter 3: Client Testimonials Chapter 4: YouTube and Face...